Telling their story of homelessness: voices of Victoria's Tent City. Issue 2 (3rd July 2017) - Young, Michael G.; Abbott, Nicole; Goebel, Emily
ABSTRACT: In a climate of reduced access to affordable and appropriate housing, tent cities have emerged as a unique solution to homelessness. Conducted with a semi-structured interview schedule, this qualitative study presents the findings of research conducted at Tent City, Victoria in 2016. Using snowball sampling, 12 residents of Tent City participated in research that revealed four themes for analysis: (1) push and pull motivations to join the encampment; (2) the role of services in resident's lives; (3) residents' experiences with the outside community; and (4) Tent City as a home community. Push factors included substance abuse, mental health problems, unemployment, family problems while pull factors included lack of affordable and appropriate housing, loss of housing, and personal issues. Residents' experiences with services were generally negative with social/health services being considered inadequate, housing options overly restrictive and controlling. The outside community was considered hostile and uninformed as the workings of Tent City and the benefits it provided. Importantly, Tent City provided both a psychological and functional sense of community for residents. While the directions for future research are many, further examination of the broader sociopolitical context in which tent cities emerge could be examined. As well, the themes identified here could be explored further in terms of how existing services could be restructured to better respond to the needs of homeless persons.